Description of a new Otacilia species from China, with transfer of two species from the genus Phrurolithus (Araneae: Corinnidae) - Hu, Dong-Sheng; Zhang, Feng (Zootaxa, 2011)
A new species, Otacilia liupan, is diagnosed, described and illustrated. Two species, Otacilia hengshan (Song, 1990) comb. nov. and O. foveata (Song, 1990) comb. nov., are transferred from the genus Phrurolithus. The male of O. foveata is reported for the first time. A distribution map of those three species is provided.